Beyond corporate incapacity, or, how I learned to stop worrying and love the ultra vires doctrine - Connolly, Niamh Áine (Trinity College (Dublin, Ireland). School of Law, 2009)
The research contained in this thesis was conducted by employing the conventional techniques of academic legal research, drawing on a variety of primary and secondary legal materials. The law governing the principal topics addressed is primarily judicial in origin. The author therefore identified and studied relevant legal authorities, of which most were cases from the Republic of Ireland and the United Kingdom as well as authorities from a number of common law jurisdictions. She also researched the relatively small number of relevant statutory provisions in all the common law jurisdictions considered. In parallel, the author conducted a comprehensive search for relevant secondary materials. These materials included textbooks, edited collections, and journal articles from many jurisdictions. A number of theses held at other universities were located and considered. Official government reports on corporate capacity proved to be an important source. The research process was aided by the use of electronic databases, which facilitated access to domestic and international case law, statute and journals, as well as the materials available in the Berkeley Library of Trinity College Dublin.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin